Pemanfaatan Aplikasi JAKI sebagai Sarana Pelaporan Keluhan Warga Jakarta terhadap Efektivitas, Tantangan, dan Implikasi Politik Digital - Alita Aura Zahir; Cendana Anabel; Muhammad Emir Adriansyah; Fatkhuri Fatkhuri; Maisarah Mitra Adrian (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The development of digital public services has encouraged the Provincial Government of DKI Jakarta to develop JAKI as a digital-based platform for public services and citizen complaints in supporting smart city and digital governance initiatives. This study aims to analyze the role of the JAKI application in improving public service effectiveness and to examine the extent to which the platform encourages public participation in digital governance in DKI Jakarta. This research employs a descriptive qualitative approach through literature review, policy document analysis, and previous studies related to digital public services and public participation. The findings indicate that JAKI has accelerated the public complaint handling process, improved accessibility to public services, and strengthened the integration of government services through a digital system. However, the form of public participation that emerges remains largely administrative and has not fully encouraged substantive citizen involvement in digital public services. In addition, the implementation of JAKI still faces several challenges, including digital literacy gaps, limited technological access, system transparency issues, and allegations of AI manipulation in responding to public complaints. This study shows that the digitalization of public services is not solely related to technological efficiency, but also to the relationship between government, society, and digital governance practices within smart governance.